An assessment of the association between therapeutic relationships and insight among those with acquired brain injury and intellectual disability - Andrea Sica; Corinne McCabe; Kevin Tierney (Discover Mental Health)
Abstract The association between therapeutic relationships (TR) and Insight into overall deficit and skill among clinical populations is supported by a very limited number of studies. Even fewer of these have explored the association in brain injury or disability populations, and none have explored the association outside of therapeutic settings with qualified professionals such as psychologists. In fact, the impact of TR on Insight when interventions are delivered by frontline, non-clinically trained staff is virtually unexplored. This explorative, correlational study of 24 adults with acquired brain injury (ABI) (N = 11) and intellectual disability (ID; N = 13) and their 24 keyworkers aimed to address this gap. The Scale To Assess Therapeutic Relationships (STAR) provided the measure of TR while the Patient Competency Rating Scale (PCRS) provided the measure of Insight. Participants were recruited from a residential community service. Spearman’s rho correlations between the STAR and PCRS and each of their subscales revealed no significant correlations in the overall sample. However, several post-hoc correlations reached statistical significance within the ABI group. These findings support the hypothesis of an interplay between TR and Insight following ABI. Reasons why this interplay was not found in the overall sample or the ID group are discussed.